Solving the Axisymmetric Inverse Heat Conduction Problem by a Wavelet Dual Least Squares Method. (17th March 2009) - Cheng, Wei; Fu, Chu-Li
Abstract : We consider an axisymmetric inverse heat conduction problem of determining the surface temperature from a fixed location inside a cylinder. This problem is ill-posed; the solution (if it exists) does not depend continuously on the data. A special project method—dual least squares method generated by the family of Shannon wavelet is applied to formulate regularized solution. Meanwhile, an order optimal error estimate between the approximate solution and exact solution is proved.